Enforced Remote Work During the Covid-19 Pandemic: The Relationship between Remote Working Intensity and Employee Motivation Using A Structural Equation Modelling Approach - Nwoko, Charles; Yazdani, Khashayar (Journal of Entrepreneurship, Business and Economics, 2022)
Since the time corona virus disease (COVID-19) outbreak was first reported in December 2019, the world has never been the same. With rapid spread of the disease, individuals, organisations and governments took steps to curtail the damage that followed including travel restrictions, social distancing and remote working. Little is known based on empirical evidence of the relationship between remote working and employee motivation. This study employed survey research design, and analysed data using structural equation modelling. Using self-determination approach, the study found that, although remote working saved commuting time for employees and improved work-life balance for most, it did not improve employee motivation. One reason for this was that remote working took employees by surprise and many saw it as forced flexibility because they had no other option and had no input in the decision to work remotely. The negative relationship between remote working and employee motivation is also connected to lack of face-to-face collaboration, inadequate peer support and social isolation. Building digital competencies require time and effort, and the frequent interruption of work due to other demands at home negatively affected work, creating stress, mental health challenges and other psychosocial risk issues. These present an opportunity for organisations to formulate and implement policies that support remote working, and ultimately improve engagement and motivational outcomes in the new normal. Research paper Keywords: Remote working, COVID-19, work from home; basic psychological needs, self-determination, motivation Reference to this paper should be made as follows: Nwoko, C., & Yazdani, K. (2022). Enforced Remote Work During the Covid-19 Pandemic: The Relationship between Remote Working Intensity and Employee Motivation Using A Structural Equation Modelling Approach. Journal of Entrepreneurship, Business and Economics , 10 (2S2), 165–200.